Integration of service quality, benchmarking and Ishikawa diagram in service operations - Adrian Noor Prayudha; Budi Harsanto (Jurnal Manajemen dan Pemasaran Jasa, 2020)
This paper aims to explore the integration of Service Quality (SERVQUAL) and two specific Total Quality Management (TQM) techniques -benchmarking and Ishikawa diagram- to improve quality in the service industry, particularly in the hospitality industry. The survey was administered to respondents at one five-star hotel in Bandung City, Indonesia. Benchmarking was conducted to compare this hotel to two other hotels at similar levels and within geographical proximity. Ishikawa analysis was then performed to analyze potential causes. The results of the study identified eleven negative score attributes (out of twenty-one) from SERVQUAL, which was in line with the benchmarking results. The Ishikawa diagram showed the root causes of these attributes and helped with developing ideas for practical quality improvements in the future. Most studies in the hospitality industry have examined SERVQUAL and TQM separately. Our study contributes uniquely to the existing literature by providing insight into the combination of SERVQUAL and two TQM specific tools to improve quality operations in a hospitality setting.